Analisis Peningkatan Kinerja Karyawan Puskesmas Rembang 2 - Tryana, Pria; Tahwin, Muhammad (Universitas Islam Kadiri, 2025)
This study was conducted at Puskesmas Rembang 2. The purpose of this study is to demonstrate the relationship between the variables of competence, motivation, and work environment with the performance of the employees at Puskesmas Rembang 2. To collect data, a questionnaire method was used. This study involved all the staff of Puskesmas Rembang 2, totaling 65 people. Saturation sampling was used in the sampling method. Subject data is the type of data used, while the source of the data is primary data—data obtained directly from the research object, namely the completion of questionnaires given to respondents. Reliability and validity tests are used to evaluate the data. On the other hand, data analysis was conducted using multiple linear regression analysis, with hypothesis testing stages using the t-test and determination test using the R2 test. The research results show that the variables of competence, motivation, and work environment significantly contribute to employee performance at Puskesmas Rembang 2. The determination test results indicate that these variables contribute 79.5% to employee performance, while other factors, not included in this study, contribute 20.5%